Beyond bath bombs: partner's response to postpartum depression. Issue 4 (2nd October 2022) - Maxwell, December; Praetorius, Regina T.; Keaton, Craig; Alam, Komal
ABSTRACT: Postpartum depression is a significant public health concern due to the physical, emotional, economic, and life course outcomes. Postpartum depression (PPD) can have multiple impacts on the mother, child development, and family. PPD severity is also influenced by social support, including partner support. Per family systems theory, each family member is not an isolated individual, but rather subject to the functioning of the family unit. Extant research focuses on maternal response to PPD, as well as recent inquiries into paternal depression. However, less known is how partners perceive postpartum depression, and more specifically, what they have done to help their partner experiencing PPD in order to restore familial equilibrium as a result of the PPD stressor. Understanding what has worked for partners of those experiencing PPD can lead to better partner-support interventions intending to reduce the impact PPD has on not only the mother, but the infant as well. As such, this study used a qualitative thematic analysis approach, with an interface of family systems and family stress theories, to analyse comments made on Reddit by partners. Themes included: just be there for her; seek outside support; understand what she goes through; and not all partners make it through.